PEMODELAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PERGURUAN TINGGI POLITEKNIK - Subyantoro, Eko; Putra, Septafiansyah Dwi (Jurnal Informatika, 2017)
Higher Education is a place for students to get an education to gain knowledge in the field of particular science. Old people entrust their children who are assets to the best colleges. For Higher Education is the belief of parents to be an option, thus it can be said parents and students are the main customers for PerguruanTinggi.Penelitian produces a CRM model for Higher Education Polytechnic to monitor the results of learning achievement so that Stakeholders can see the learning results both academic and nonacademic. Information systems development methodology FAST is a development with a functional analysis of parts associated with the system. The fast method can be developed to facilitate the making of CRM model in Polytechnic.Â Keywords: CRM, Fast Methodology, Perguruan Tinggi Politeknik